Volume 6B: Energy 2014
DOI: 10.1115/imece2014-38679
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic and Aeroelastic Analyses of a Wind Turbine Blade Modeled as a Thin-Walled Composite Beam

Abstract: In this paper, dynamic and aeroelastic analysis of a wind turbine blade modeled as an anisotropic composite thin-walled box beam is carried out. The analytical formulation of the beam is derived for the flapwise bending, chordwise bending and transverse shear deformations. The derivation of both strain and kinetic energy expressions are made and the equations of motion are obtained by applying the Hamilton’s principle. The equations of motion are solved by applying the extended Galerkin method (EGM) for anti-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…More recently, Librescu and Song [3] have published one of the most comprehensive studies on the theory of thin-walled composite beams extended with linear and nonlinear treatments. Together with these well-established theories, various other studies addressing the effect of transverse shear deformation on the free vibration of thin-walled composite beams have also been reported [3][4][5][6][7][8] and showed that transverse shear effect plays a crucial role in the accurate prediction of dynamic behavior, especially for rotating beams [9]. Within this respect, we investigated the effect of transverse shear deformation on the free vibration of rotating blades modeled as thin-walled composite beams.…”
Section: Introductionmentioning
confidence: 81%
“…More recently, Librescu and Song [3] have published one of the most comprehensive studies on the theory of thin-walled composite beams extended with linear and nonlinear treatments. Together with these well-established theories, various other studies addressing the effect of transverse shear deformation on the free vibration of thin-walled composite beams have also been reported [3][4][5][6][7][8] and showed that transverse shear effect plays a crucial role in the accurate prediction of dynamic behavior, especially for rotating beams [9]. Within this respect, we investigated the effect of transverse shear deformation on the free vibration of rotating blades modeled as thin-walled composite beams.…”
Section: Introductionmentioning
confidence: 81%